SISTEM INFORMASI BORANG AKREDITASI PROGRAM STUDI BERBASIS WEB - Purnamasari, Susan Dian; Nasir, Muhammad (JURNAL ILMIAH MATRIK, 2017)
The accreditation form of the study program is the reference used for the process of quality assessment and feasibility study program conducted by the National Accreditation Board of Higher Education (BAN PT). To be able to assess the study program will arrange an accreditation form which contains questions about the process that runs in the study program. Filling in the form according to the criteria specified by BAN PT in seven standards. In the study only on standard data management 6 on financing, facilities and infrastructure and 7 on research and community service. Because it involves interrelated data, then the system created will integrate the data scattered and web-based. This form of filling system can also make an automatic assessment of quantitative form fields. As for the content that is normative then made the field of assessment based on the criteria set in book 6 on the assessment matrix. Keywords: Borang, Accreditation, BAN PT, Information System